A Comparative Compositional Study of 7th- to 11th-Century Copper-Alloy Pins from Sedgeford, England, and Domburg, the Netherlands. Issue 2 (3rd July 2018) - ROXBURGH, MARCUS A; VAN OS, BERTIL J H
Abstract : EARLY MEDIEVAL PINS are found in large quantities on both sides of the North Sea and the English Channel, and as a result are one of the few artefact types that can facilitate the exploration of cross-cultural contacts in terms of style, material and manufacture. This paper presents the results of the analyses of two contemporary groups of copper-alloy pins dating from the 7th to the 11th centuries using X-ray fluorescence spectrometry. One group of pins considered here was recovered from an excavated Anglo-Saxon settlement at Sedgeford (Norfolk), while the other derives from a coastal settlement at Domburg (Zeeland, the Netherlands). We argue here, on the basis of our results, that while pin production may have been focused around major mercantile, royal or ecclesiastical centres, it was also localised in terms of materials and production methods, suggesting potentially different trajectories in each region for the development and control of specialist production.